Resilience and Religious Coping as Moderators in The Interaction of Trait Anxiety and Pain Catastrophizing - Afini Wirasenjaya; Sali Rahadi Asih (Lembaga Penelitian Universitas YARSI, 2022)
Chronic pain in young adults can affect daily activity ranging from interfering with work productivity, restricting social life, intruding on developmental tasks, lessening the quality of life, to triggering psychological disorders. This condition can be worse if individuals with chronic pain have anxiety issue that makes them engage in pain catastrophizing, i.e., thinking about the pain fatally. In discussing chronic pain, previous studies sought the negative factors around pain experience. Nowadays, professionals pay more attention to the positive factor, like resilience (ability to bounce back). Besides, when dealing with negative life events, Indonesian also tend to implement religious culture, values, and practices. In this study, the author examines the role of resilience and religious coping as moderators in the interaction of trait anxiety and pain catastrophizing. A total of 275 individuals with chronic pain aged 18-35 participated in this study. Participants informed their consent and filled out a set of questionnaires that described their pain experiences. The regression analysis results show that positive religious coping has a moderating role in the interaction of trait anxiety and pain catastrophizing. Having a good connection with God or a higher being, as well as others and oneself, can help chronic pain patients deal with their pain. From this finding, professionals can consider positive religious coping an intervention target when helping chronic pain patients.